Analysis of Trip Generation and Attraction Model in South Tangerang City - Budiman, Arief; Bethary, Rindu Twidi; Suzanti, Wiwien; Kusuma, Fadiah Indriani (JURUSAN TEKNIK SIPIL, 2024)
South Tangerang City encounters a significant increase of population every year, due to the rapid development of South Tangerang City. The increase in population causes a high demand for housing, jobs, and more. These needs cause many land uses changing function. Land use change must be accompanied by transportation planning so it does not cause traffic problems like congestion. The generation model is the early stage of urban transportation planning, the modelling of trip generation and attraction in South Tangerang City is carried out to find out the factors causing the trip generation and attraction in this city and to gain the best model. The parameters of the model is the land use in the city that was received from the government of South Tangerang City. The analysis was made in stages starting from validity and reliability test, correlation test, linearity test, and the final one is multiple linear regression test with stepwise method type 1. Based on the analysis result, the factor that has the greatest influence on trip generation in South Tangerang City is number of primary educational facilities (elementary school, islamic elementary school, junior high school, and islamic junior high school) (X3) with the selected model is Y1 = 1129,265 + (383,198) X3 and the value of R2 = 0,809. Furthermore, the factor that has the greatest influence on trip attraction in South Tangerang City is number of hospitals (X6) with the selected model is Y2 = 69668,640 – (3372,120) X6 and the value of R2 = 0,826.